Antioxidant Effects of DPP-4 Inhibitors in Early Stages of Experimental Diabetic Retinopathy - Hugo Ramos; Patricia Bogdanov; Jordi Huerta; Anna Deàs-Just; Cristina Hernández; Rafael Simó (MDPI AG, 2022)
Hyperglycemia-induced oxidative stress plays a key role in the impairment of the retinal neurovascular unit, an early event in the pathogenesis of DR. The aim of this study was to assess the antioxidant properties of topical administration (eye drops) of sitagliptin in the diabetic retina. For this purpose, db/db mice received sitagliptin or vehicle eye drops twice per day for two weeks. Age-matched db/+ mice were used as the control group. We evaluated retinal mRNA (RT-PCR) and protein levels (Western blotting and immunohistochemistry) of different components from both the antioxidant system (NRF2, CAT, GPX, GR, CuZnSOD, and MnSOD) and the prooxidant machinery (PKC and TXNIP). We also studied superoxide levels (dihydroethidium staining) and oxidative damage to DNA/RNA (8-hydroxyguanosine immunostaining) and proteins (nitrotyrosine immunostaining). Finally, NF-кB translocation and IL-1β production were assessed through Western blotting and/or immunohistochemistry. We found that sitagliptin protected against diabetes-induced oxidative stress by reducing superoxide, TXNIP, PKC, and DNA/RNA/protein oxidative damage, and it prevented the downregulation of NRF2 and antioxidant enzymes, with the exception of catalase. Sitagliptin also exerted anti-inflammatory effects, avoiding both NF-кB translocation and IL-1β production. Sitagliptin prevents the diabetes-induced imbalance between ROS production and antioxidant defenses that occurs in diabetic retinas.